If you want to scare yourself - Sommer-Bodenburg, Angela; Spiess, Helga (New York : Lippincott, 1989)
Bored and sick in bed, Freddy listens to four scary stories told to him by members of his family and then makes one up himself.
Translation of: Wenn du dich gruseln willst.
3.6
3-6
Keywords: Sick -- Fiction; Horror stories; Storytelling -- Fiction; Short stories; Sick -- Fiction; Storytelling -- Fiction; Short stories; Horror -- Fiction